Studi Komparatif Perlindungan Data Pribadi dalam UU ITE 2024 dan UU PDP 2022 - Ghufron Rosadi Hidayah; Ha. Djazim Ma’shum; Muhammad Awaluddin (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The development of digital technology has had a significant impact on people's lives, including the protection of citizens' privacy rights. One key issue that has emerged is the management and protection of personal data, which is increasingly vulnerable to misuse. This study aims to examine and compare the personal data protection provisions stipulated in the 2024 Electronic Information and Transactions Law (ITE Law) and Law Number 27 of 2022 concerning Personal Data Protection (PDP Law). The research method used is a normative approach with comparative study techniques. The study focuses on the legal substance, scope of data protection, and institutional roles in implementing both regulations. The analysis shows that the ITE Law remains general in nature, lacking specific detailed regulations governing personal data protection mechanisms. Meanwhile, the PDP Law presents a more systematic and comprehensive specific regulation, referencing international principles such as the General Data Protection Regulation (GDPR) in the European Union. However, several implementation challenges exist, including overlapping authority between institutions, inconsistencies in legal norms, and limited adequate legal infrastructure. This situation has the potential to create regulatory dualism and complicate the law enforcement process. Therefore, steps are needed to harmonize the ITE Law and the PDP Law, strengthen the capacity of institutions responsible for data protection, and increase the digital literacy of the public so that citizens' digital rights can be optimally protected in the digital era.